Experimental Tailer like Thermal Lag Engine to obtain pressure and volume diagrams//Motor de Lag Térmico experimental tipo Tailer para obtener diagramas de presión y volumen - Fernández-Aballí-Altamirano, Carlos; Calcoen, Michaël; Vandermeersch, Edward; González-Bayón, Juan J. (Ingeniería Mecánica. Revista electrónica. ISSN 1815-5944, 2012)
Abstract The Thermal Lag Engine (TLE) patented by Peter Tailer’s is briefly introduced. The discussion about the thermodynamic working principle of this external combustion machine is presented. For this work the claims in literature have been studied by the authors to design and develop an experimental installation with the objective of measuring for the first time the pressure-volume (pV) relationship of a TLE as described by Tailer and West. The pV diagrams are presented here and support previous theoretical claims about the TLE. Their triangular form shows the effects described by West in the expansion and compression processes caused by the variation of the cold heat transfer area. Also the relationship between the heat transfer capacity of the engine and its working frequency becomes apparent from the measurements, indicating that larger heater areas and limited cold heat transfer characteristics allow more work production per cycle at higher operating frequencies. Key words: thermal lag engine, pressure-volume diagrams, external combustion engines. _______________________________________________________________________________ Resumen Se introduce brevemente el Motor de Lag Térmico (MLT) patentado por Peter Tailer y se esboza el debate científico sobre la termodinámica de esta máquina de combustión externa. A partir del estudio de los distintos puntos de vista los autores de este trabajo desarrollaron una instalación experimental con el objetivo de medir por primera vez la relación presión-volumen (pV) de un MLT como el descrito por Tailer y West. Los diagramas pV son presentados y apoyan los planteamientos teóricos previos sobre los MLT. Su forma triangular muestra los efectos descritos por West sobre los procesos de compresión y expansión debido a la exposición variable del área fría de intercambio de calor. Las mediciones pV muestran la relación que existe entre la capacidad de intercambio de calor del motor y su frecuencia de operación. Estas indican que más áreas de transferencia de calor en el lado de la fuente y una transferencia limitada hacia el sumidero aumentan la producción de trabajo a mayores frecuencias de operación. Palabras claves: motor de Lag térmico, diagramas de presión y volumen, motor de combustión externa.